Molecular and neurological characterizations of three Saudi families with lipoid proteinosis - Al-Fakey Yasser H; Van Maldergem Lionel; McGrath John A; Liu Lu; Alorainy Ibrahim A; Alrasheed Saleh; Abu-Amero Khaled K; Salih Mustafa A; AlSuhaibani Adel H; Oystreck Darren T; Bosley Thomas M (BMC, 2011)
Abstract Background Lipoid proteinosis is a rare autosomal recessive disease characterized by cutaneous and mucosal lesions and hoarseness appearing in early childhood. It is caused by homozygous or compound heterozygous mutations in the ECM1 gene. The disease is largely uncharacterized in Arab population and the mutation(s) spectrum in the Arab population is largely unknown. We report the neurologic and neuroradiologic characteristics and ECM1 gene mutations of seven individuals with lipoid proteinosis (LP) from three unrelated consanguineous families. Methods Clinical, neurologic, and neuro-ophthalmologic examinations; skin histopathology; brain CT and MRI; and sequencing of the fullECM1 gene. Results All seven affected individuals had skin scarring and hoarseness from early childhood. The two children in Family 1 had worse skin involvement and worse hoarseness than affected children of Families 2 and 3. Both children in Family 1 were modestly mentally retarded, and one had typical calcifications of the amygdalae on CT scan. Affected individuals in Families 2 and 3 had no grossneurologic, neurodevelopmental, or neuroimaging abnormalities. Skin histopathology was compatible with LP in all three families. Sequencing the full coding region of ECM1 gene revealed two novel mutationsin Family 1 (c.1300-1301delAA) and Family 2 (p.Cys269Tyr) and in Family 3 a previously described 1163 bp deletion starting 34 bp into intron 8. Conclusions These individuals illustrate the neurologic spectrum of LP, including variable mental retardation, personality changes, and mesial temporal calcificationand imply that significant neurologic involvement may be somewhat less common than previously thought. The cause of neurologic abnormalities was not clear from either neuroimaging or from what is known about ECM1 function. The severity of dermatologic abnormalities and hoarseness generally correlated with neurologic abnormalities, with Family 1 being somewhat more affected in all spheres than the other two families. Nevertheless, phenotype-genotype correlation was not obvious, possibly because of difficulty quantifying the neurologic phenotype and because of genetic complexity.